Screening for alkaline keratinolytic activity in fungi isolated from soils of the biosphere reserve “Parque Costero del Sur” (Argentina) - Elíades, Lorena Alejandra (2010)
A screening was carried out on 69 fungal strains isolated from alkaline-calcareous, neutral and alkaline-sodic soils, as well as from their associated plant material, to determine their ability to grow at alkaline pH. A total of 32 fungi were selected for their ability to produce alkaline keratinase activity in submerged shaken cultures supplemented with soybean meal (SM) and tryptone and on cow hair (CH) under solid state fermentation conditions. Although several fungal strains produced keratinolytic activity on both SM and CH, they differed in the levels detected. Among them, Aspergillus niger, Cladosporium cladosporioides, Metarrhizium anisopliae, Neurospora tetrasperma and Westerdikella dispersa were the best producers, with levels higher than 1.2 U ml⁻¹. Different fungal species are here reported for the first time for their ability to produce keratinolytic activity at alkaline pH.